Digital information product development: lessons from a small-sized German enterprise (INMR - Innovation & Management Review, 2021)
Purpose – This case study examines the new product development (NPD) process of digital informationproducts (DIPs) and its critical success factors (CSFs) in a small-sized German enterprise.Design/methodology/approach – A case study was conducted with a small firm focused on thedevelopment of DIPs; data were obtained through semi-structured interviews, direct observation anddocument analysis.Findings – The firm uses an informal and cross-functional NPD process (idea generation, idea validation,product creation and product launch) in converting an idea into a sellable product. Peculiar aspects of eachstage within the process as well as ten CSFs to NPD projects were verified.Research limitations/implications – Limitations are attributed to its qualitative nature, which doesnot allow generalizations, though careful attention was given to validity and reliability issues through the useof data source triangulation.Practical implications – The paper provides a conceptual process that may benefit further initiatives fordeveloping and launching DIPs, as well as a comprehensive list of CSFs for such projects.Originality/value – This paper is the first one to schematize the NPD process and practices for DIPs, aswell as key capabilities. It contributes to the NPD literature in discussing dynamic aspects that are typical tothe firm analyzed and to others operating in a digital context. At the same time, it reinforces other traditionalaspects that have become overlooked in digital business debates.